Localized surface plasmon resonance on nano cube- nano sphere dimer - Hasan, Md. Mehedi; Rahman, Ofsora; Shama, Tasfia Tabassum (BRAC Univeristy, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.